A Novel Interaction Between the TLR7 and a Colchicine Derivative Revealed Through a Computational and Experimental Study - Francesco Gentile; Marco A. Deriu; Khaled Barakat; Andrea Danani; Jack Tuszynski (MDPI AG, 2018)
The Toll-Like Receptor 7 (TLR7) is an endosomal membrane receptor involved in the innate immune system response. Its best-known small molecule activators are imidazoquinoline derivatives such as imiquimod (R-837) and resiquimod (R-848). Recently, an interaction between R-837 and the colchicine binding site of tubulin was reported. To investigate the possibility of an interaction between structural analogues of colchicine and the TLR7, a recent computational model for the dimeric form of the TLR7 receptor was used to determine a possible interaction with a colchicine derivative called CR42-24, active as a tubulin polymerization inhibitor. The estimated values of the binding energy of this molecule with respect to the TLR7 receptor were comparable to the energies of known binders as reported in a previous study. The binding to the TLR7 was further assessed by introducing genetic transformations in the TLR7 gene in cancer cell lines and exposing them to the compound. A negative shift of the IC50 value in terms of cell growth was observed in cell lines carrying the mutated TLR7 gene. The reported study suggests a possible interaction between TLR7 and a colchicine derivative, which can be explored for rational design of new drugs acting on this receptor by using a colchicine scaffold for additional modifications.